Making sense of Arab labor markets: The enduring legacy of dualism - Ragui Assaad (IZA Journal of Labor & Development, 2014)
It is well-established that Arab labor markets share certain common characteristics, including an oversized public sector, high youth unemployment, weak private sectors, rapidly growing but highly distorted educational attainment, and low and stagnant female labor force participation. I argue in this paper that all of these features can be explained by the deep and persistent dualism that characterizes Arab labor markets that resulted from the use of labor markets by Arab regimes as tool of political appeasement in the context of "authoritarian bargain" social contracts. Even as fiscal crises have long destabilized these arrangements in most non-oil Arab countries, culminating in the dramatic political upheavals of the Arab Spring, I argue that the enduring legacy of dualism will continue to strongly shape the production and deployment of human capital in Arab economies for some time.
Keywords: I25; J21; J24; J31; J45; O53; P52; 330; Labor market dualism; Arab Spring; Unemployment; Education; Authoritarian bargain